Mekanisme Jual Beli Emas Online di Platform Tokopedia Emas Perspektif Hukum Islam - Alifia Rizky Amalia; Fikri Firmanto; Hanivatul Hanivatul; Rahmad Salim (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Digital gold transactions on Tokopedia have become a popular modern investment option due to their convenience and flexibility. However, the legality of these transactions from an Islamic perspective remains debated, creating uncertainty for Muslim investors. This study examines Tokopedia Emas's online gold trading practices through the lens of Islamic law. Using a descriptive qualitative approach, the research gathered data through interviews, literature review, and content analysis. The findings suggest that while Tokopedia's gold trading practices generally comply with Sharia principles, the majority of scholars still consider them invalid, or haram. This is primarily due to the lack of immediate physical delivery of the gold and the presence of non-cash and installment-based transactions, which could lead to usury (riba). Although the DSN-MUI Fatwa Number 77/DSN-MUI/V/2010 permits such transactions, the study advises Muslims to avoid any form of trade that could involve usury. Therefore, it concludes that online gold transactions, as conducted on this platform, do not align with Islamic legal standards.